Pengembangan Multimedia Interaktif Berbasis Aplikasi Google Sites pada Materi Indahnya Keberagaman di Negeriku dalam Pembelajaran PPKn Kelas IV sebagai Penguatan Literasi Budaya dan Kewargaan - Agung Ryanto; Puspa Djuwita; Abdul Muktadir (UNIB Press, 2023)
This study aims to describe the development of Google Sites on the beautiful material of diversity in my country in class IV PPkn learning as a reinforcement of cultural and civic literacy. The type and method of research used in this study is development research. The subjects of the study were grade IV students of SD Negeri 03 Ujan Mas as an experimental class and grade IV students of SD Negeri 09 Ujan Mas as a control class. Data collection techniques use interviews, surveys and tests. Research instruments use needs analysis instruments, expert validation instruments, product test instruments, product effectiveness test instruments. Data analysis in this study was carried out by analyzing expert validity data, rater/researcher agreement, instrument development, effectiveness analysis (Normality Test, Homogeneity Test and N-Gain). Based on the results of the study, it can be concluded that interactive multimedia based on the Google Sites application developed according to material expert validators, design validators and language validators is declared feasible for use. From the learning outcomes of grade IV students of SD 03 Ujan mas, it is known that the effectiveness of interactive multimedia products based on the Google Sites application that has been developed shows an increase as a reinforcement of cultural and civic literacy in class IV PPKn learning on the beautiful material of diversity in my country.